Pengaruh Akuntabilitas, Partisipasi Dan Pengawasan Terhadap Kinerja Anggaran Berkonsep Value For Money Pada Badan Pengelolaan Keuangan Dan Aset Daerah Kabupaten Bengkalis - Zakaria Batubara; Ria Risna (JAS (Jurnal Akuntansi Syariah), 2020)
The purpose of this research was to determine partially and simultaneously the influence of accountability, public participation and supervision of budget performance with the concept of value for money in the Bengkalis District Financial and Asset Management Agency. This research uses descriptive quantitative analysis method. The sampling technique uses boring sampling method. The data analysis technique used is multiple linear of regression. The results showed that partial accountability, participation and supervision had a positive and significant effect on budget performance with the concept of value for money in the Bengkalis District Financial and Asset Management Agency. While simultaneously accountability, participation and supervision have a positive and significant effect on budget performance with the concept of value for money in the Regional Financial and Asset Management Agency in Bengkalis Regency with a 93.5% influence.